2022
DOI: 10.1021/acsabm.2c00177
|View full text |Cite
|
Sign up to set email alerts
|

Visual Monitoring of Nucleic Acid Dynamic Structures during Cellular Ferroptosis Using Rationally Designed Carbon Dots with Robust Anti-Interference Ability to Reactive Oxygen Species

Abstract: Ferroptosis triggered by an iron-dependent accumulation of lipid reactive oxygen species (ROS) has drawn widespread attention. Directly visualizing the dynamic structures of nucleic acids during the ferroptosis of cells is of great importance considering their vital roles in numerous biological functions. However, direct imaging remains challenging, largely due to the extremely high concentrations of ROS generated during ferroptosis, which can affect the imaging of nucleic acid targeted fluorescent probes. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The TEM (HRTEM), AFM, XRD, XPS, and TGA characterizations were done using the apparatus described in ref . The FTIR, UV–vis absorption, PL, PLQY, and PL lifetime tests of YCPDs used the equipment as described previously (ref ). EPR spectra were measured on a Bruker E550 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEM (HRTEM), AFM, XRD, XPS, and TGA characterizations were done using the apparatus described in ref . The FTIR, UV–vis absorption, PL, PLQY, and PL lifetime tests of YCPDs used the equipment as described previously (ref ). EPR spectra were measured on a Bruker E550 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of CPDs, citric acid (CA) and urea have been widely acknowledged as classical preparation systems , while urea derivatives as precursors are rarely reported. The urea derivatives currently used are semicarbazide, hydroxyurea, and benzoylurea, , which provide a great possibility for the biological functionalization of CPDs. However, the study of disubstituted urea as a precursor has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[49] Huang et al developed nucleic acid-responsive carbon dots (CDs) for monitoring the dynamic structures of nucleic acids during ferroptosis (Figure 2c). [50] These CDs are composed of two precursors, m-phenylenediamine (m-PD) and aminourea hydrochloride (Figure 2d). The former not only provides a green emission wavelength but also contains multiple nitro- gen atoms that could form hydrogen bonds with nucleic acids, endowing CDs with nuclei-targeting ability.…”
Section: Nucleimentioning
confidence: 99%
“…e) Confocal images of the nuclei of CDs‐incubated cells during ferroptosis. Reprinted with permission from [50]. Copyright 2020 American Chemical Society.…”
Section: Detecting Ferroptosis At Different Levelsmentioning
confidence: 99%
See 1 more Smart Citation